2001
DOI: 10.1097/00004032-200109000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Radon Exposure and the Risk of Leukemia

Abstract: Since the 1990's, several authors estimated that radon inhalation may deliver a small amount of irradiation to the red bone marrow, and consequently may increase the risk of leukemia in humans. The objective of this review is to conduct a critical analysis of epidemiologic results currently available concerning the relationship between radon exposure and the risk of leukemia. Nineteen ecological studies, six miner cohort studies, and eight case-control studies published between 1987 and 2000 are included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Previous case–control studies have reported participation < 55%, and exposure measurements were often limited to subsets of study participants (Cartwright et al 2002; Kaletsch et al 1999; Lubin et al 1998; Maged et al 2000; Steinbuch et al 1999; Stjernfeldt et al 1987). In contrast with ecological studies, we had information on a number of potential individual-level confounders (Laurier et al 2001; Tong et al 2012), although adjusting for these variables did not materially affect hazard ratios, suggesting little or no confounding by these factors although we cannot completely exclude residual confounding due to misclassification in the confounder variables. This is consistent with the current knowledge on childhood cancer etiology: There is evidence of increased risks among children with a genetic predisposition and among those exposed to high doses of ionizing radiation (e.g., applied for cancer treatment), but little evidence of environmental risk factors (Belson et al 2007; Eden 2010; McKinney 2005; Pollack and Jakacki 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous case–control studies have reported participation < 55%, and exposure measurements were often limited to subsets of study participants (Cartwright et al 2002; Kaletsch et al 1999; Lubin et al 1998; Maged et al 2000; Steinbuch et al 1999; Stjernfeldt et al 1987). In contrast with ecological studies, we had information on a number of potential individual-level confounders (Laurier et al 2001; Tong et al 2012), although adjusting for these variables did not materially affect hazard ratios, suggesting little or no confounding by these factors although we cannot completely exclude residual confounding due to misclassification in the confounder variables. This is consistent with the current knowledge on childhood cancer etiology: There is evidence of increased risks among children with a genetic predisposition and among those exposed to high doses of ionizing radiation (e.g., applied for cancer treatment), but little evidence of environmental risk factors (Belson et al 2007; Eden 2010; McKinney 2005; Pollack and Jakacki 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, because these were population-level analyses, control for individual-level confounders was not possible. Results of case–control studies have been inconsistent (Laurier et al 2001; Tong et al 2012), with some studies reporting an association (Maged et al 2000; Raaschou-Nielsen et al 2008) and others not (Cartwright et al 2002; Kaletsch et al 1999; Kendall et al 2013; Lubin et al 1998; Steinbuch et al 1999; Stjernfeldt et al 1987). A recent analysis of a Danish case–control study reported evidence that air pollution from road traffic might enhance the association between radon and childhood leukemia (Bräuner et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As stated in several reviews (Laurier et al 2001; Raaschou-Nielsen 2008; Tong et al 2012), most of the studies found positive correlations with radon, whereas no evidence was found for gamma radiation exposure. Population-based case–control studies that included interviews and in-home measurements have reported mixed results, mostly nonsignificant (Raaschou-Nielsen 2008), but their interpretation is hindered by the generally limited participation rates and the subsequent potential for selection bias.…”
Section: Introductionmentioning
confidence: 92%
“…Nevertheless, at present, no effect other than lung cancer can be ascribed to radon exposure [50]. For leukaemia, numerous studies have been performed, but a positive association suggested by ecological studies has not been confirmed by studies based on individual data [60, 61]. …”
Section: Review Of Health and Biological Effectsmentioning
confidence: 99%